From Adaptation To Transformation? Empowerment, Culture, And Social Capital In Derawan’s Butonese Fishing Community (International Journal of Environmental Sciences, 2025)
This article examines how cultural values and social capital shape processes of empowerment among Butonese migrant fishers in Derawan Island, Berau Regency, East Kalimantan, Indonesia. While empowerment in small-scale fisheries is often framed in terms of livelihood improvement, this study argues that empowerment is best understood as a layered and contested process—anchored in resources, agency, and achievements (Kabeer, 1999), mediated by social capital (Putnam, 1993, 2000), and legitimized through symbolic cultural repertoires (Bourdieu, 1986). Drawing on ethnographic fieldwork conducted in 2023–2024 across five settlements, the study combines participant observation, in-depth interviews, and documentary analysis to explore how Butonese migrants negotiate belonging and recognition in a multiethnic coastal frontier.Findings reveal that empowerment manifests in both social and economic domains: collective organization for infrastructure and decision-making, partial participation in village forums, diversification of livelihoods, and women’s growing role in processing and trade. Cultural values such as padoma (collective work) and binci-binciki kuli (mutual respect) provide solidarity, conflict management, and legitimacy, but also reproduce hierarchies that limit youth and women’s agency. Social capital operates as an indispensable safety net, market channel, and governance resource, yet its benefits are unevenly distributed, often controlled by patrons and community elites. Ultimately, empowerment remains partial—resilient yet stratified, solidaristic yet politically constrained.The article contributes conceptually by demonstrating the ambivalence of empowerment in migrant fishing communities: it is not only about material gains but also about the cultural and symbolic resources that shape authority and belonging. Empirically, it enriches scholarship on coastal migration and empowerment in Indonesia through fine-grained ethnography. Practically, it highlights the need for inclusive governance strategies that democratize social capital, reinterpret cultural values in transformative ways, and strengthen bridging ties between migrant communities and formal institutions.